WASH to control COVID-19: A rapid review - Khatib, Mahalaqua Nazli; Sinha, Anju; Mishra, Gaurav; Quazi, Syed Ziauddin; Gaidhane, Shilpa; Saxena, Deepak; Gaidhane, Abhay M.; Bhardwaj, Pankaj; Sawleshwarkar, Shailendra; Zahiruddin, Quazi Syed (Frontiers in Public Health, 2022)
Background Preventive public health has been suggested as methods for reducing the transmission of COVID-19. Safety and efficacy of one such public health measure: WASH intervention for COVID-19 has not been systematically reviewed. We undertook a rapid review to assess the effect of WASH intervention in reducing the incidence of COVID-19. Methods We conducted searches in PubMed, MEDLINE, and EMBASE. We undertook screening of studies in two stages and extracted data and assessed the quality of evidence for the primary outcome using GRADE recommendations. Main results We included a total of 13 studies with three studies on COVID-19 and 10 on SARS. The study found that hand washing, sterilization of hands, gargling, cleaning/shower after attending patients of COVID-19, or SARS was protective. Evidence also found that frequent washes can prevent SARS transmission among HCWs. However; one study reported that due to enhanced infection-prevention measures, front-line HCWs are more prone to hand-skin damage. The certainty of the evidence for our primary outcome as per GRADE was very low. We did not find any studies that assessed the effect of WASH on hospitalizations, and mortality due to COVID-19. Also; we did not find any study that compared WASH interventions with any other public health measures. Conclusions Current evidence of WASH interventions for COVID-19 is limited as it is largely based on indirect evidence from SARS. Findings from the included studies consistently show that WASH is important in reducing the number of cases during a pandemic. Timely implementation of WASH along with other public health interventions can be vital to ensure the desired success. Further good-quality studies providing direct evidence of the efficacy of WASH on COVID-19 are needed.